Consumer Data Protection Amidst the Rise of Online Loan Services: Safeguarding Personal Data Privacy - Ramadhan, Muhammad Tri Andika; Fitri, Winda; Agustianto, Agustianto (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2024)
In today's rapidly advancing technological era, safeguarding personal data is paramount in ensuring the privacy and security of individuals while preventing misuse or unauthorized access to their private information. As information technology and the internet continue to evolve, personal data has become a highly valuable asset for many companies and organizations. Threats to the security of personal data, such as irresponsible data dissemination in online lending operations, have the potential to lead to a host of serious issues, including identity theft, financial fraud, privacy breaches, and identity theft. The research method employed here is the normative legal research method. In Indonesia, the protection of personal data is governed by Law Number 27 of 2022 concerning Personal Data Protection. This law provides a crucial legal framework for safeguarding the privacy and security of citizens' personal information, with clear definitions and broad scope. Its aim is to protect individuals' rights related to the collection, use, processing, storage, and deletion of personal data by involved parties. The foundation of personal data protection regulation in Indonesia also rests on the principle that personal data protection is a fundamental human right that is inviolable, as recognized and respected by the 1945 Constitution of the Republic of Indonesia. The Personal Data Protection Law has established criminal sanctions for offenders, such as those involved in personal data theft or unauthorized data dissemination, with the hope of deterring such actions and upholding the privacy and security of individuals' personal data.